Seminar Parenting: Menghadirkan Kebahagiaan Di Rumah: Mempraktikkan Joyfulness Dalam Kehidupan Sehari-Hari - Sidiq, Nurul Jamiah; Kurnia R, Rika; Bachtiar, Muhammad Yusri; Manga, Delvhina; Bakri, Tri Sugiarti M (LPPI UMN AL WASHLIYAH, 2025)
Seminar on